Hepatoprotective Effect of Moringa Oleifera Lam. Leaf on Biochemical Parameters Against Paracetamol Induced Hepatotoxicity in Rats (Journal of Chittagong Medical College Teachers' Association, 2016)
Moringa Oleifera Lam (Called Shajna in Bengali) is a plant which has a long history of uses in liver disorders in this subcontinent. This study was done to evaluate the hepatoprotective effects of ethanol extract of leaf of this plant on paracetamol induced hepatotoxicity in albino rats. The total experiments were designed as follows I) Experiment- (Part I):- Induction of hepatotoxicity by single administration of paracetamol at a dose of 2 gm/kg body weight. 2) Experiment- (Part II). Effects of ethanol extract of Moringa oleifera Lam. on paracetamol induced hepatotoxicity in albino rats. The biochemical reports suggested that acute administration of paracetamol produced significant hepatotoxicity in experimental rats which was evidenced by significant increase in serum bilirubin, serum alanine aminotransferase (ALT) serum aspartate aminotransferase (AST) serum alkaline phosphatese (ALP) level, decrease in serum albumin and serum total protein level. When rats were treated with extracts of M. oleifera leaf in paracetamol induced hepatotoxic albino rats, the results showed marked reduction in serum bilirubin, serum ALT, serum AST and serum ALP level and increase of serum albumin level but not sigificant increase of total protein as compared with paracetamol treated group. The results of the present study revealed that ethanol extract of Moringa oleifera Lam. leaf has got protective effects against paracetamol induced hepatotoxicity. Further study is needed to find out the curative effect and to isolate the active principle and to explore out the exact hepatoprotective mechanism of this leaf extract.JCMCTA 2016 ; 27 (1) : 55 - 58